2022
DOI: 10.1093/ofid/ofac129
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Frailty and Prefrailty in People With Human Immunodeficiency Virus Aged 50 or Older: A Systematic Review and Meta-Analysis

Abstract: Background With effective antiretroviral therapy, there is an emerging population of adults aged 50 years or older with human immunodeficiency virus (HIV). Frailty is an increasingly recognized clinical state of vulnerability associated with disability, hospitalization, and mortality. However, there is a paucity of large studies assessing its prevalence in people with HIV (PWH) aged 50 or older. Methods PubMed was systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 67 publications
1
17
2
Order By: Relevance
“…Within the fields of geriatrics and HIV, the most common way to define frailty is based on the Fried Frailty Phenotype (FFP), which identifies frail individuals as those with at least three of the following characteristics: exhaustion, reduced muscle strength, low physical activity, slow walking speed, and unintentional weight loss (Fried et al, 2001). The prevalence of frailty among PLWH aged 50 years and above in a recent systematic review and meta-analysis ranges from 8.1% to 14.2% (Yamada et al, 2022). In addition, the onset of frailty is nearly 10 years earlier in PLWH compared with those without HIV (Desquilbet et al, 2007; Levett et al, 2016).…”
mentioning
confidence: 99%
“…Within the fields of geriatrics and HIV, the most common way to define frailty is based on the Fried Frailty Phenotype (FFP), which identifies frail individuals as those with at least three of the following characteristics: exhaustion, reduced muscle strength, low physical activity, slow walking speed, and unintentional weight loss (Fried et al, 2001). The prevalence of frailty among PLWH aged 50 years and above in a recent systematic review and meta-analysis ranges from 8.1% to 14.2% (Yamada et al, 2022). In addition, the onset of frailty is nearly 10 years earlier in PLWH compared with those without HIV (Desquilbet et al, 2007; Levett et al, 2016).…”
mentioning
confidence: 99%
“… 21 , 22 , 23 The observed frailty prevalence in this study is lower in comparison to what is reported by two systematic reviews on the subject: the most recent being by Yamada and collaborators reporting a pooled prevalence of 10.9%. 24 , 25 However, when contextualizing the observed results, it is important to consider that this comparatively lower prevalence of frailty has already been reported in another Mexican study. 22 Nevertheless, other findings such as the observed prevalence of disability for mobility, multimorbidity, as well as a very low proportion of participants without any GS, are still remarkable, as this remains a relatively young population.…”
Section: Discussionmentioning
confidence: 60%
“…Studies show that frailty and prefrailty appear more often and at an earlier age in people living with HIV than in the general population and can reach up to 28.6% and 47.2% respectively. 8,[13][14][15] This can be explained by several factors including the persistent chronic inflammation caused by HIV, other HIV-related factors such as low CD4 cell count, higher rates of comorbidities (eg. cardiovascular, metabolic, osteoporosis) than in the general population, as well as higher rates of smoking and intravenous drug use (IDU) among PLWH.…”
Section: Frailty In Plwhmentioning
confidence: 99%